Evaluation of Interactions Between Transient Receptor Potential Vanilloid 1 and Active Constituents Using Molecular Docking - Sahar Jaffal; Salman Khan; Muhammad Ibrar Khan (Dubai Medical Journal)
Introduction: Pain, whether acute or chronic, imposes huge economic burdens in the societies due to complexities in the signaling pathways that lead to pain. There are many nociceptive receptors and channels that play key roles in the processing and maintenance of pain. Transient receptor potential vanilloid 1 (TRPV1) is a nonselective cation channel that is considered a crucial target in pain. Drugs that are available in the market have side effects, highlighting the need to find new analgesics that have no side effects.